2017
DOI: 10.1097/icu.0000000000000376
|View full text |Cite
|
Sign up to set email alerts
|

Refractive error in underserved adults

Abstract: Purpose of Review To evaluate the epidemiology of uncorrected refractive errors (URE) in adults both in the US and globally, health outcomes impacted by URE, common barriers to treatment, and propose potential interventions. Recent Findings URE is the main cause of visual impairment (VI) and the second leading cause of blindness globally. Rates of URE are rising, and cause disability that reduces productivity, economic earnings, and the quality of life of affected individuals. Economic barriers, health care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 48 publications
3
26
0
Order By: Relevance
“…Uncorrected Refractive Errors (URE) are the main cause of visual impairment and the second leading cause of preventable blindness globally, 47 while in some recent studies URE is considered as the main leading cause of VI. 8 , 22 , 24 , 32 In Saudi Arabia URE were reported to be a leading cause of VI in adults of Northern Saudi Arabia 33 and commonest cause of VI in school children of Qassim Province.…”
Section: Causes Of Visual Impairmentmentioning
confidence: 99%
“…Uncorrected Refractive Errors (URE) are the main cause of visual impairment and the second leading cause of preventable blindness globally, 47 while in some recent studies URE is considered as the main leading cause of VI. 8 , 22 , 24 , 32 In Saudi Arabia URE were reported to be a leading cause of VI in adults of Northern Saudi Arabia 33 and commonest cause of VI in school children of Qassim Province.…”
Section: Causes Of Visual Impairmentmentioning
confidence: 99%
“…Lack of knowledge and awareness about RE3, non-recognition of the problem at personal or family level, as well as at community and public health level; economic and social barriers and availability and affordability of eye health services are the main reasons for RE to remain uncorrected 4,5. RE have serious impact on economy of many countries of the world 6,7.…”
Section: Introductionmentioning
confidence: 99%
“…Although previous studies demonstrated the relationship between economic status and the prevalence of UREs, the unmet refractive error, and the use of spectacles in different parts of the world,6, 10, 16, 19 to the best of our knowledge, no study has investigated economic inequity in unmet refractive error. Horizontal equity is defined as “equal treatment for equal medical needs regardless of some characteristics such as economic status, gender, health status, etc” 20, 21…”
Section: Introductionmentioning
confidence: 95%
“…Some studies reported the prevalence of UREs, the percentage of the unmet refractive error, and the use of spectacles in different parts of the world, especially in Asia 2, 10, 11, 12, 13, 14. These studies found that the prevalence of unmet refractive error is remarkable, as well as the factors which are effective on them 6, 10, 11, 15, 16. Some also suggested that UREs are distributed unequally especially among the individuals with a low economic status and suburban population 3, 17, 18…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation